Critical analysis and predictive models using the physicochemical characteristics of cassava processing wastewater generated in Brazil. (June 2022) - Costa, Renata Carvalho; Ramos, Márcio Daniel Nicodemos; Fleck, Leandro; Gomes, Simone Damasceno; Aguiar, André
Abstract: Cassava is industrially processed to produce several food items (e.g. flour and starch), but the processing methods generate liquid residues that can be highly polluting. This study seeks to conduct a literature review on the characteristics of cassava processing wastewaters (CPWW) generated in Brazil, which is one of the world's leading producers of Cassava. This was done to suggest more adequate ways for treating the effluent and to obtain predictive models that can aid professionals in characterizing this effluent. The results show that CPWW contain high concentrations of organic matter, besides nutrients (nitrogen and phosphorous), solids, and cyanide. Based on its characteristics, CPWW has been evaluated as an alternative feedstock for obtaining biofuels, fertilizers, pesticides, etc. In addition, the results show that flour production results in effluents with higher concentrations of pollutants than starch production. This is because starch production uses more water per ton of processed cassava. The average BOD5 /COD ratios for flour production (0.49) and for starch extraction effluents (0.47) show that they are highly biodegradable. Furthermore, after analyzing the relationship between organic matter and nutrient concentrations (C:N:P), the results indicate that anaerobic biological processes are more suitable for treating this waste. To corroborate this, stabilization ponds (covered or not) have been the most used treatments in Brazil. There was a significant linear correlation between COD and BOD5 (R 2  > 0.8), suggesting that BOD5 can be estimated from COD in CPWW generated through different factories. Graphical abstract: Unlabelled Image Highlights: Cassava processing generates effluent rich in organic matter, cyanide, N, and P. Concentration of pollutants is higher than discharge standards into water bodies. BOD5 /COD and C:N:P values indicate the suitability of anaerobic biological treatments. High linear correlation between COD and BOD5 (R 2  > 0.8) suggests a predictive model.